(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Sepsis is a systemic inflammatory response syndrome (SIRS) that is triggered by infection. On the other hand, multiple organ dysfunction syndrome (MODS) is the failure of critical organ function in patients suffering from SIRS. Because SIRS and SDOM are consequences of excessive inflammatory activation. The aim of this article is to provide a review of some pathophysiological aspects of the SRIS / SDOM construct of infectious origin, using the acute cholangitis as an example of this chain of events.